Quantum dynamics of Renner-Teller and isotopic effects in NH(a1?) + D(2S) reactions - Defazio, Paolo; Gamallo, Pablo; Akpinar, Sinan; Petrongolo, Carlo (Royal Soc Chemistry, 2011)
A quantum dynamics study for the NH(a(1)Delta) + D(S-2) reactions using coupled channel time dependent real wavepacket formalism is presented. Moreover, the Renner-Teller (RT) interactions between two electronic states of NHD((X) over tilde (2) A '' and (A) over tilde (2) A') have been taken into account by means of semiempirical RT matrix elements. The introduction of RT effects opens the possibility of studying not only the adiabatic reactions [depletion (d) to N(D-2) + HD(X-1 Sigma(+)) and exchange (e) to ND(a(1)Delta) + H(S-2)] but also nonadiabatic ones [quenching (q) to NH(X-3 Sigma(-)) + D(S-2) and exchange-quenching (eq) to ND(X-3 Sigma(-)) + H(S-2)]. Reaction probabilities, cross sections, isotopic effects, and rate constants are presented for all the before mentioned reactions. RT results are compared with Born-Oppenheimer, quasiclassical, and experimental data. Contrasting with previous NH + H results, we point out interesting RT and isotopic effects, which depend on the D and H masses and on the tunneling of the H atom. In fact, RT effects, near-threshold cross sections, and rate constants are smaller in NH + D than in NH + H, as expected from the masses of the attacking atoms. Our rate constants and quenching branching ratio agree well with previous quasiclassical and experimental data, validating the semiempirical RT coupling we employ. Some small differences between calculated and measured rate constants might be due to the theoretical approximations and to the large experimental error bars.
Keywords: Real Wave-Packets; Scattering; Nh2